Korelasi Pra-Pemahaman Gadamer Dengan Syarat Dan Adab Mufassir - Muhammad Aminullah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2023)
This research aims to reveal the correlation between Gadamer's pre-understanding and mufassir terms and manners. This type of research is qualitative in the form of library research. The approach used is an interpretive approach. The data used is primary data sourced from books and scriptures, and secondary data includes related works and other references that can support research, which are then processed and analyzed. The results of the research show that in the dialectical process, an interpreter must have a pre-understanding that already exists and is formed within him, in the form of art, history, world view, experience, sharpness of mind, the external world, spirituality, expressions, styles, and symbols. However, according to Gadamer, pre-understanding must be criticized so that it does not go beyond the meaning of the text, so that what he calls